Estudio comparativo del pensamiento crítico de los estudiantes de la carrera de Psicología Educativa y Psicopedagogía de la Universidad Nacional de Chimborazo - Pomaquiza Pomaquiza, Rubén Darío (2021)
The current research project had the general objective to analyze the relationship of critical thinking dimensions in Educational Psychology and Psychopedagogy students. Critical thinking in university education is essential because it allowsstudentsto interpret, analyze and develop their conclusions, which benefit learning. The methodology used had a quantitative approach, with a non-experimental design, of a fundamental and field type, with a descriptive-correlational level. The population was made up of the students of the Educational Psychology and Psychopedagogy career. Its sampling was nonprobabilistic and intentional which was detailed with 11 men and 29 women; the technique was the psychometric test, the Watson-Glaser Critical Thinking Appraisal test instrument, the same one that through the analysis of the results it was possible to reach the conclusion that is contrasted that Educational Psychology students have a medium level concerning the global evaluation of critical thinking, inference, recognition of assumptions, interpretation, and evaluation of arguments. In contrast, in deduction, they have a high level. Psychopedagogy students at a global level and recognition of assumptions have a medium and high level, in the inference; in the deduction medium, in the interpretation medium, and the evaluation of arguments is high. Therefore, it can be attributed that psychopedagogy students have better developed their critical thinking compared to Educational Psychology students.